Konseling Keluarga untuk Mewujudkan Keharmonisan Rumah Tangga - Adif Jawadi Saputra; Rita Sinthia; Atikah Mahfuza Pangat; Wan Chalidaziah (Prodi Bimbingan dan Konseling Islam, 2023)
Abstrak Every individual wants family harmony in forming a family. Awareness of role and function and acceptance of existence and existence become a strong foundation in running a household. In realizing a harmonious household, there are often problematic phenomena in the family such as quarrels, jealousy, infidelity, income differences, differences in life principles and leading to the act of lending the marriage lor lthe divorce or lproblems that occur lin lthe life of lthe household lshould lbe resolved lso that lthe harmony of lthe family lremains land lis realized. The increase in the rarity of divorce has raised the issue of the decline in the value of family harmony and the institution of the family is not always a good place for children's development. The line research is a library research approach which is sourced from books about realizing household harmony using family counseling. With the approach of family counseling, it is used as an intervention process for problems that interfere with family harmony. Family counseling tries to build closer relationships, individuals who are able to control their emotions, and families who always have good communication in realizing family harmony. Keywords: Family counseling, Family harmony l